2016
DOI: 10.1007/s11270-016-2804-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ecological Properties of Petroleum Oil-Contaminated Soil After Low-Temperature Thermal Desorption Treatment

Abstract: Effects of low-temperature thermal desorption (LTTD) treatment on the ecological properties of soil contaminated by petroleum hydrocarbons were assessed. For this purpose, various ecological properties related to soil health and physicochemical properties of the oil-contaminated soil before and after LTTD treatment were investigated. Total petroleum hydrocarbon concentration, electrical conductivity, organic matter, and total nitrogen decreased while water-holding capacity and available P 2 O 5 increased. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…Though many of the spills were relatively small (<10 barrels), nearly all affected agricultural land, including cropland, pastureland, and natural grasslands. The petroleum hydrocarbons (PHC) in the crude oil reduce productivity potential of the land (Eom, Rast, Veber, & Vasseur, ; Issoufi, Rhykerd, & Smiciklas, ; Yi, Park, Munster, Kim, & Sung, ), necessitating contaminant removal (i.e., soil remediation) to return to pre‐spill levels. Returning these lands to productivity (i.e., soil reclamation) is crucial for long‐term food security, especially as other important agricultural land in the state is declining in productivity due to salinity and sodicity issues (Seelig, ).…”
Section: Introductionmentioning
confidence: 99%
“…Though many of the spills were relatively small (<10 barrels), nearly all affected agricultural land, including cropland, pastureland, and natural grasslands. The petroleum hydrocarbons (PHC) in the crude oil reduce productivity potential of the land (Eom, Rast, Veber, & Vasseur, ; Issoufi, Rhykerd, & Smiciklas, ; Yi, Park, Munster, Kim, & Sung, ), necessitating contaminant removal (i.e., soil remediation) to return to pre‐spill levels. Returning these lands to productivity (i.e., soil reclamation) is crucial for long‐term food security, especially as other important agricultural land in the state is declining in productivity due to salinity and sodicity issues (Seelig, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper there were applied thermal methods of remediation in the laboratory: combustion and thermal desorption and successive extraction with solvents using petroleum ether and benzene. There authors are concerned about testing multiple types of soils [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Terefe et al (2008) who suggested that silt-and clay-sized particles formed sand-sized aggregates through a cementing effect at thermal temperatures of 300-500 °C. However, a lower temperature (250 °C) or shorter thermal treatment duration (10 min) may not significantly change the composition of soils as observed by Yi et al (2016). The pH of HOC after LTTD was increased (p < 0.05) and closer to neutral, as compared to base soil and HOC before treatment.…”
Section: Changes In Physicochemical Properties Of Obdcsmentioning
confidence: 78%
“…According to the treatment temperatures, they are classified as low-temperature (100-350 °C) and hightemperature (350-600 °C) thermal desorption by physical separation, and incineration (600-1000 °C) which destroys contaminants (Falciglia et al, 2011). On one hand, limited reusability of residual soil after treatment and high initial setup expenses restrain the practicability of high-temperature thermal desorption (HTTD) (Yi et al, 2016). On the other hand, low-temperature thermal desorption (LTTD) treatment represents a feasible method for the remediation of oil contaminated soils which both achieves relatively complete remediation and keeps soil health at the maximum extent.…”
Section: List Of Figuresmentioning
confidence: 99%
See 1 more Smart Citation